Assessing the Suitability of Polyethylene Terephthalate (PET) in Bituminous Concrete Mixes - Chaudhary M.; Saboo N.; Gupta A. (My University, 2025)
This research deals with the use of waste plastic (PET) as a partial bitumen replacement in bituminous concrete mixes at different binder contents. In this study, two methods of plastic addition, i.e. dry process and wet process are used at PET contents varying from 0 to 10% by bitumen weight. A comparative analysis is also conducted between the wet process and the dry process of adding plastic. The consistent increase in Marshall stability up to 8% PET content and then a decrement at 10% PET signifies the upper polymer dosage at 8%. The higher values of TSR at all PET contents concerning the neat binder indicate the improved moisture sensitivity of the mixes as a result of PET addition. In addition to that the dry process of PET addition was found better than the wet process for all the scenarios. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.